Characterization of Incorporating RAP Materials to the Asphalt Layers of Pavement Structure - Abdalhameed, Abdalsattar; Abd, Duraid (Iraqi Journal of Civil Engineering, 2022)
Recycling the old paving waste and reusing it in the construction of new highways was resorted to, and this is a good step from an economic point of view, as well as from an environmental and health point of view, as it reduces carbon emissions and eliminates a large amount of disposable reclaimed asphalt pavement materials (RAP). This study aims to evaluate the best layer of pavement structure; base, binder, and surface layers for inclusion (RAP) materials based on stability and indirect tensile strength. In addition, highlight the best percentage that can be added from RAP to achieve positive results and better than that associated reference mixture in terms of Marshall test and Indirect tensile strength test RAP materials collected from different sources Karbala and Fallujah, were adopted in this study at percentages of 20%, 30%, and 40% by weight of the asphalt mixture. Two scenarios of incorporating RAP materials have been adopted : The first is considered that RAP as a black rock in which the effect of aged binder surrounding the aggregate of RAP is neglected while the second is not considered RAP as black rock and the influence of aged binder in RAP materials has been taken into consideration. Dora bitumen has been adopted in the current study which is used commonly in Iraq.  It has been highlighted that the best layer in which RAP can be incorporated is the base layer, with a percentage up to 40% that RAP without considering RAP black rocks regardless of the sources of RAP